Over-expression and analysis of two Vitis vinifera carotenoid biosynthetic genes in transgenic Arabidopsis - Brackenridge, Anika Elma (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Wine Biotechnology))--University of Stellenbosch, 2006.